Agronomic Biofortification of Zinc in Pakistan: Status, Benefits, and Constraints - Rehman, Abdul; Farooq, Muhammad; Ullah, Aman; Nadeem, Faisal; Im, Seon Young; Park, Sang Koo; Lee, Dong-Jin (Frontiers in Sustainable Food Systems, 2020)
Micronutrient malnutrition (e.g., zinc) is one of the major causes of human disease burden in the developing world. Zinc (Zn) deficiency is highly prevalent in the Pakistani population (22.1%), particularly in women and children (under 5 years) due to low dietary Zn intake. In Pakistan, wheat is the primary staple food and is poor in bioavailable Zn. However, the number of malnourished populations has decreased over the last decade due to multiplied public awareness, accelerated use of Zn fertilizers (particularly in wheat and rice), initiation of several national/international research initiatives focusing on Zn biofortification in staple crops and availability of supplements and Zn fortified meals merchandise, nonetheless a large number of people are facing Zn or other micronutrient deficiencies in the country. There are few reports highlighting the significant increase in daily dietary Zn uptake in population consuming biofortified wheat (Zincol-2016) flour; indicating the positive prospect of biofortification interventions up scaling in lowering the risk of dietary Zn deficiency in rural and marginalized communities. Zinc fertilizer strategy has not only helped in enhancing the grain Zn concentration, but it also helped in improving crop yield with high economic return. In addition, Zn biofortified seeds have exhibited strong inherent ability to withstand abiotic stresses and produce higher grain yield under diverse climatic conditions. However, there are many constraints (soil, environment, genetic diversity, antinutrients concentration, socioeconomic factors etc.) that hinder the success of biofortification interventions. This review highlights the status of Zn deficiency in Pakistan, the success of agronomic and genetic biofortification interventions. It also discusses the economics of agronomic biofortification and cost effectiveness of Zn fertilization in field conditions in Pakistan and the potential of Zn biofortified seeds against abiotic stresses. Furthermore, it also highlights the constraints which limit the sustainability of biofortification interventions.